Remote Sensing and Digital Image Processing with R - Lab Manual - Alves, Marcelo De Carvalho; Sanches, Luciana (Boca Raton CRC Press, 2023)
This Lab Manual is a companion to the textbook Remote Sensing and Digital Image Processing with R. It covers examples of natural resource data analysis applications including numerous, practical problem-solving exercises, and case studies that use the free and open-source platform R. The intuitive, structural workflow helps students better understand a scientific approach to each case study in the book and learn how to replicate, transplant, and expand the workflow for further exploration with new data, models, and areas of interest. $1!# s
Keywords: Remote sensing -- Data processing; Image processing -- Digital techniques; Geographic information systems